Infectious Complications Following Cochlear Implant: Risk Factors, Natural History, and Management Patterns. (22nd February 2022) - Moon, Peter K.; Qian, Z. Jason; Ahmad, Iram N.; Stankovic, Konstantina M.; Chang, Kay W.; Cheng, Alan G.
Abstract : Objective: To describe the natural history, detail the treatment patterns, and identify the risk factors for cochlear implant (CI) infections in a large US cohort. Study Design: Retrospective study based on insurance claims. Setting: Optum Data Mart database: 6101 patients who received CIs from 2003 to 2019. Methods: Infections, treatments patterns, and timelines were described. A multivariable logistic regression model was used to assess the association between postoperative oral antibiotics and CI infection. Results: The cohort includes 4736 (77.6%) adults and 1365 (22.4%) children. Between adult and pediatric patients, rates of CI infection (5.1% vs 4.5%, P =. 18) and explantation (1.2% vs 0.8%, P =. 11) were not significantly different. Infections typically occurred within 5 months of surgery. Children were diagnosed with CI infection earlier than adults (median difference, –1.5 months; P =. 001). Postoperative oral antibiotic supply was not associated with lower risk of CI infection in either children or adults. However, among adults, otitis media was associated with higher odds of CI infection (odds ratio, 1.41; P <. 001), while higher income was associated with lower odds of CI infection (odds ratio, 0.71; P =. 03). Conclusions: Postoperative oral antibiotics were not associated with lower risk of infection or interventions. Otitis media episodes and lower income were associated with increased risk of infection among adults as well as intervention overall. Infection typically presented within the first 6 months after surgery, with children presenting earlier than adults. Overall, our findings serve as a resource for providers to consider in their care of patients with CIs.